The use of innovative technology in the preparation of future teachers in Pedagogical Universities (Pedagogy of Higher and Secondary Education, 2013)
Gorodys’ka V. V. The use of innovative technology in the preparation of future teachers in Pedagogical Universities.This article analyzes the innovative technologies in preparing future educators at Pedagogical Universities and emphasizes the need of the multimedia using as a means of teaching and case-technology as a teaching method because they contribute the significant amount of knowing information, familiarizes with the latest educational technologies, and meet students' modern requirements – future educators of children establishments.
Keywords: education innovation; multimedia technology; multimedia presentations; case-method; preparation of future educators